Dynamic force/motion simulation of a rigid-flexible manipulator during task constrained - Ata, Atef A; Johar , Habib (2004)
Constrained motion of a rigid-flexible manipulator in contact with a rotating environment is considered. A rigid-flexible manipulator may be assigned tasks in a moving environment where the winds or vibrations affect the position and/or orientation of surface of operation. When the environment is moving, knowledge of the angle a between the contact surface and the horizontal is required at every instant to evaluate the contact force and the rqured torques for a specific atsk. In this paper, different profiles for the time varying angle a are proposed to investigate the interaction between the joints profile and the angular motion of the constrained surface and the effect of this change into the contact force and the joint torques of a rigid-flexible manipulator.